P065: Emergency department staff perceived need and preferred methods for communication skills training. (May 2019) - Howlett, M.; Mostofa, M.; Talbot, J.; Fraser, J.; Atkinson, P.
Abstract : Introduction : Burnout includes emotional exhaustion (EE), depersonalization (DP) and personal accomplishment (PA). Emergency Department (ED) staff have high levels of burnout that may be responsive to communication skills training. We surveyed ED staff perception of need and efficacy before and after an intervention using an established conflict resolution methodology.Methods : ED physicians, nurses and support staff were surveyed at two regional hospitals using the Maslach Burnout Inventory (MBI) and a communications questionnaire to establish the perceived need for communication skill training. Participants from one center were provided with a communications intervention (Crucial Conversations®, VitalSmarts®), and a refresher course 6-15 months later. The survey was then repeated at both sites and course participant feedback was elicited.Results : MBI results were high (mean EE = 25.25 (high > 25), 95% CI = 22.5-28; DP = 11.6 (high > 8), 95% CI = 10.1-13.2; PA = 35.85 (low <34), 95% CI = 34.3-37.4). Initially 82% of intervention and 77% of control site participants responded that "attending an educational session about ways to communicate better would help the participants at work". Post intervention group responses to "The program will be helpful to me in communicating more effectively in my work environment" were: 75% "strongly agree" and 25% "agree". No rating below "agree" was assigned by any of the participants. Participants preferred facilitated small group simulations and advocated for earlier career implementation.Conclusion : There was a perceived need for and impact from communication skills training for ED staff with high measured burnout. Training may be best implemented in small group simulated encounters and in health professional education curriculum or as part of work orientation.